2009
DOI: 10.1021/ie801295y
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Potential Microflora-Activated Carrier for a Colon-Specific Drug Delivery System and Its Characteristics

Abstract: A novel polyelectrolyte complex (PEC) formed by sodium cellulose sulfate (NaCS) and chitosan was prepared as a potential material for a colon-specific drug delivery system. The characteristics of NaCS-chitosan film were measured by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), in vitro degradation, and in vitro drug release experiments. SEM data indicated that the NaCS-chitosan film had relatively homogeneous and smooth morphology at the initial state and deformed after be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Due to its favorable biological properties, including nontoxicity, biocompatibility, biodegradation, hydrophilicity, and good film-forming performance [4,[21][22][23][24][25], NaCS has been received much attention and widely used in many fields, especially in pharmaceutical and biomedical engineering. In particular, NaCS was frequently used as a polyanion encapsulation matrix to immobilize enzymes, microorganisms and animal/plant cells or as a swellable hydrophilic matrix applied in the drug delivery system which forms a gel layer when exposed to aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its favorable biological properties, including nontoxicity, biocompatibility, biodegradation, hydrophilicity, and good film-forming performance [4,[21][22][23][24][25], NaCS has been received much attention and widely used in many fields, especially in pharmaceutical and biomedical engineering. In particular, NaCS was frequently used as a polyanion encapsulation matrix to immobilize enzymes, microorganisms and animal/plant cells or as a swellable hydrophilic matrix applied in the drug delivery system which forms a gel layer when exposed to aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…4, under the weak acidic condition of pH 6.4, chitosan/NaCS/TPP microcapsules showed a regular drug release behavior with a trend of slowly increasing, and the BSA was released sustainably and almost completely during 10 h. However, the control microcapsules had a burst drug release (more than 63.1±0.7%) effect during the first hour and the drug released irregularly during the 10 h study, which was not suitable for use as a sustained drug carrier according to the Ritger-Peppas model [13] (less than 60.0%). Since PEC formed with chitosan and NaCS was a hydrophilic and swellable system, and can be degraded by the enzyme in SCF [3,5], the drug release would be a combination of diffusion and macromolecular relaxation processes followed by the erosion procedures of the system [14]. The chitosan/NaCS/TPP microcapsules prepared here could be used as a protein carrier in a further appropriate formulation for controllable release of drug in colon.…”
Section: In Vitro Release Of Proteinmentioning
confidence: 99%
“…Sodium cellulose sulfate (NaCS) as a novel hydrophilic cellulose derivative is a polyanionic polymer, which has favorable biological properties as a drug carrier material, such as hydrosolubility, nontoxicity, biodegradability and good film-forming ability [2]. We have found that the polyelectrolyte complex (PEC) composed of chitosan and NaCS has the potential behaviors in the controlled release of drugs, and was used for preparing the colon-specific drug delivery capsules [3], the multilayer microcapsules [4], and the complex films [5]. However, chitosan/NaCS microcapsules tend to collapse, since NaCS with high molecular weight only binds on the surface of chitosan droplets [6].…”
Section: Introductionmentioning
confidence: 99%
“…This complex was used as an excipient to prepare a controlled release gastroretentive system of "tablets-in-capsule" based on the combination of different mini-tablets (Gómez-Burgaz et al, 2008). Capsules of chitosan-sodium cellulose sulfate showed a potential use for delivery of 5-aminosalicylic acid specifically to the colon (Wang et al, 2009). The swelling of the system and the drug release rate were dependent on chitosan molecular weight and environment pH.…”
Section: Chitosan Complexed With Other Polysaccharidesmentioning
confidence: 99%